From structure to story: semantic mapping and narrative documentation of Riyadh’s modern architecture - Alghamdi, Naif; Alnaim, Mohammed Mashary (Frontiers in Built Environment, 2025)
IntroductionRiyadh’s modern architecture from the 1970s–1980s, produced during the post-oil transformation, remains critically underrepresented within Saudi heritage narratives, which primarily emphasize either pre-modern vernacular structures or contemporary iconic developments. This study addresses a conceptual and methodological gap in heritage documentation by proposing a framework that interprets modern architecture as an evolving narrative of cultural memory and urban identity rather than a stylistic category.MethodsThe research develops and applies a hybrid documentation model integrating urban morphology analysis, semantic mapping, and participatory narrative documentation. This interpretive system draws on community workshops, semi-structured interviews (n = 12), on-site observations, and archival materials to examine four case studies in Riyadh: two governmental, one institutional, and one hospitality. Data were analyzed through open and axial coding, forming semantic clusters that linked spatial form with cultural meaning.ResultsThe findings reveal that Riyadh’s modern architecture embodies negotiated identities that mediate between localized tradition and global modernity. The Saudi Central Bank and Ports Authority express institutional power and bureaucratic control; the Equestrian Club and the Riyadh Palace Hotel illustrate civic participation, openness, and aspirational modernity. Semantic mapping and narrative inquiry exposed how users’ memories and symbolic associations transform these buildings from static artifacts into cultural texts embedded within the collective urban consciousness.DiscussionThe hybrid documentation model extends existing integrative frameworks by operationalizing them through participatory and interpretive tools that connect lived experience with spatial analysis. It demonstrates that documentation can function as both method and theory, an act of cultural mediation that merges the tangible and the intangible. The model offers a replicable, low-cost, and contextually sensitive framework adaptable to other rapidly urbanizing, non-Western settings.